2018
DOI: 10.1002/asna.201813526
|View full text |Cite
|
Sign up to set email alerts
|

On the ephemeris of the eclipsing polar HU Aquarii. II: New eclipse epochs obtained 2014–2018

Abstract: The magnetic cataclysmic variable HU Aquarii displayed pronounced modulations of its eclipse timing. In recent years, these have been intensively modeled and discussed in the framework of planets orbiting the binary or the Applegate effect. No scenario yielded a unique and satisfactory interpretation of the data. Here, we present 26 new eclipse epochs obtained between 2014 and 2018. The steep and continuous decrease of the orbital period observed in the time interval 2010-2013 has slowed down sometimes before … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The CV type, period, mass ratio, and secondary are from Ritter & Kolb (2003)'s catalogue, which was last updated on Dec 31, 2015. Orbital periods for V603 Cas, J1544+2553, RW Sex, UU Aql, V380 Oph, QZ Ser, SU UMa, QZ Vir and EI Psc are from Thoretensen et al (2017), for TW Vir from Dai et al (2017), for HU Aqr from Schwope & Thinius (2018) and for AR UMa from Bai et al (2016). The latter also found that an AlI absorption line doublet in the visual varied.…”
Section: Acknowledgementsmentioning
confidence: 86%
“…The CV type, period, mass ratio, and secondary are from Ritter & Kolb (2003)'s catalogue, which was last updated on Dec 31, 2015. Orbital periods for V603 Cas, J1544+2553, RW Sex, UU Aql, V380 Oph, QZ Ser, SU UMa, QZ Vir and EI Psc are from Thoretensen et al (2017), for TW Vir from Dai et al (2017), for HU Aqr from Schwope & Thinius (2018) and for AR UMa from Bai et al (2016). The latter also found that an AlI absorption line doublet in the visual varied.…”
Section: Acknowledgementsmentioning
confidence: 86%
“…Eclipse timings from the polar HU Aqr initially suggested multiple planet candidates orbiting the close binary (Qian et al 2011). However, extending the observation baseline revealed timing variations that could not be explained solely by a multiple planet hypothesis (Schwope & Thinius 2014, 2018. The source of this timing variability remains uncertain.…”
Section: Introductionmentioning
confidence: 92%
“…There have been attempts to explain orbital variations seen in eclipsing binaries through the Applegate mechanism (Applegate 1992;Lanza 2006), where a magnetically active late-type companion redistributes its angular momentum via changes in its subsurface magnetic field. Estimates of the connection between changes in the quadrupole moment of the secondary and the resulting variation in the orbital period of the binary suggest that the Applegate mechanism is near the limit of explaining the amplitude of the O − C variations in HU Aqr (Schwope & Thinius 2018). However, a combination of planets and the Applegate mechanism could work for HU Aqr (Bours et al 2014).…”
Section: Possible Sources Of Timing Changesmentioning
confidence: 99%
See 2 more Smart Citations